Performance of Geopolymer Concrete with Combined Use of Sodium Hydroxide and Potassium Hydroxide (International Journal of Innovative Research in Engineering & Management, 2023)
ABSTRACT- From the beginning, binders such as red  mud mortar, lime mortar, cement mortar, etc., played a  major role. It has been found that the production of cement  increases the quantity of uncontrollable CO2 emissions.  Another adhesive that can be used in place of cement is  geopolymer. Because geopolymer concrete may reduce  carbon emissions, the concrete business could grow  sustainably and prosper as a result. This technology has the  potential to reduce CO2 emissions from the construction  sector by up to 80%. To make the binder for geo polymer  concrete, alkaline solutions are used to activate sources of  materials rich in silica (Si) and aluminium (Al), such as fly  ash, GGBS, etc. Geopolymer-made concrete includes no  cement at all. In this study, we attempted to determine the compressive  strength and durability properties of geopolymer concrete  using various molarities of 8M, 10M, and 12M along with  Sodium Silicate solution. The alkaline activators used were  Sodium hydroxide (NaOH), Potassium hydroxide (KOH),  and combination of both (50%NaOH + 50%KOH). To  achieve the highest pH value for better mechanical and  durability characteristics, chemical analysis is done. After 7  and 28 days of age, the Compression and Permeability  experiments were conducted. The GPC's strength and  durability characteristics were contrasted with those of  conventional concrete.
Keywords: Geopolymer Concrete; flyash; Sodium Hydroxide; Potassium Hydroxide; Sodium Silicate; compressive strength; permeability test